Mediation Effect of Competitive Advantage on Marketing Environment and Product Creativity on Marketing Performance - Lustono Lustono; Fadhil Ghani Lusaputra; Ilma Dhiyaulhayi Al-Lust (Department of Economics Education, Faculty of Economics, Universitas Negeri Makassar, 2026)
The aim of this research is to examine the mediating effect of competitive advantage on the relationship between the marketing environment and product creativity on marketing performance. This type of research is quantitative research with a survey method. The number of samples studied in this study was 150 samples of Batik MSMEs in Banjarnegera Regency. Technique: Purposive sampling technique, the data collection method used was a questionnaire. The data analysis technique uses Structural Equation Modeling (SEM) with the SmartPLS program. The results of this research show that the marketing environment and Product Creativity partially have a positive and significant effect on Competitive Advantage. marketing environment, Product Creativity and Competitive Advantage partially have a positive and significant effect on marketing performance. Competitive Advantage is able to mediate the influence of the marketing environment on marketing performance. Competitive Advantage is able to mediate the influence of Product Creativity on marketing performance.